Suberoylanilide Hydroxamic Acid Attenuates Autoimmune Arthritis by Suppressing Th17 Cells through NR1D1 Inhibition - Da Som Kim; Hong-Ki Min; Eun Kyung Kim; Seung Cheon Yang; Hyun Sik Na; Seon-Yeong Lee; Jeong-Won Choi; Kyung-Ah Jung; Seung-Ki Kwok; Sung-Hwan Park; Mi-La Cho (Hindawi Limited, 2019)
Rheumatoid arthritis (RA) is a type of systemic autoimmune arthritis that causes joint inflammation and destruction. One of the pathological mechanisms of RA is known to involve histone acetylation. Although the histone deacetylase (HDAC) inhibitor suberoylanilide hydroxamic acid (SAHA) can attenuate arthritis in animal models of RA, the mechanism underlying this effect is poorly understood. This study was performed to examine whether SAHA has therapeutic potential in an animal model of RA and to investigate its mechanism of action. Collagen-induced arthritis (CIA) mice were orally administered SAHA daily for 8 weeks and examined for their arthritis score and incidence of arthritis. CD4+ T cell regulation following SAHA treatment was confirmed in splenocytes cultured under type 17 helper T (Th17) cell differentiation conditions. Clinical scores and the incidence of CIA were lower in mice in the SAHA treatment group compared to the controls. In addition, SAHA inhibited Th17 cell differentiation, as well as decreased expression of the Th17 cell-related transcription factors pSTAT3 Y705 and pSTAT3 S727. In vitro experiments showed that SAHA maintained regulatory T (Treg) cells but specifically reduced Th17 cells. The same results were obtained when mouse splenocytes were cultured under Treg cell differentiation conditions and then converted to Th17 cell differentiation conditions. In conclusion, SAHA was confirmed to specifically inhibit Th17 cell differentiation through nuclear receptor subfamily 1 group D member 1 (NR1D1), a factor associated with Th17 differentiation. The results of the present study suggested that SAHA can attenuate CIA development by inhibition of the Th17 population and maintenance of the Treg population through NR1D1 inhibition. Therefore, SAHA is a potential therapeutic candidate for RA.